STRATEGI PENGEMBANGAN DAN PROMOSI OBJEK DAYA TARIK WISATA RUMAH TUA DESA SEMBIRAN KECAMATAN TEJAKULA KABUPATEN BULELENG PROVINSI BALI - Mahendra, I Gede Deni; Rahmawati, Putu Indah (Universitas Pendidikan Ganesha, 2025)
Sembiran Village is one of the oldest villages in Bali with great potential as a cultural tourism destination, particularly through the old traditional houses that hold significant historical and cultural value. However, this potential remains underdeveloped due to inadequate infrastructure, weak promotional efforts, and suboptimal tourism management. This study aims to identify the current state of tourism in Sembiran Village and formulate development and promotional strategies for the old house as a primary tourist attraction. A qualitative descriptive approach was employed, with data collected through observation, in-depth interviews, and documentation from six key informants, including village officials and tourism managers. The findings reveal that while the cultural attractions in Sembiran are strong, they are not yet supported by adequate amenities, accessibility, and ancillary services. Development strategies are directed toward cultural and environmental preservation, capacity building of human resources, strengthening institutional coordination, infrastructure improvements, and digital-based promotions. This study recommends a participatory and collaborative approach involving government, local communities, and private stakeholders to develop Sembiran Village into a sustainable and competitive cultural tourism destination.